Analisis Relevansi Nilai PSAK No. 30 (Revisi 2007) tentang Sewa, Dinilai Berdasarkan Reaksi Pasar Modal - Dewi Kartika (Jurnal Vokasi Indonesia, 2013)
ABSTRACT. As one of the IFRS convergence program, DSAK-IAI has made several revisions of financialaccounting standards, one of which is PSAK No. 30 (Revisi 2007) about Leases. These financial accountingstandards have become effective since January 1, 2008. But until now still a few companies that apply thisstandard. This is probably because the company did not know the financialbenefitofthe applicationofthisstandard. Thereforethis studywas conducted to determinethe value relevance of PSAK No.30 (Revised2007) about Leases, which is assessed on the basis of capital market reactions.The results showedthat theapplication of PSAK No.30 (Revised 2007), about Leases, do nothave aninfluence onthe market. So we can saythe market does notsee thevalue relevance of PSAK No.30 (Revised2007) about Leases.Key words: Value relevance, PSAK No. 30 (Revisi 2007) about Leases.